Los precedentes del tribunal constitucional en el arbitraje - Ledesma Narvaez, Marianella Leonor (2020)
The arbitration in our country has been impacted by the decisions of the Constitutional Court. These decisions have had such importance in the arbitration activity, not only because of the content of the interpretations, but because these interpretations have been given the connotation or precedent status. Precisely, it is the reason for this work to present the two precedents that the Court has set in arbitration to reflect on how successful are the rules of jurisprudential creation and how these statements impact on legal security.